Diseño e implementación de un sistema domótico para la generación de confort en la residencia de adultos mayores “Hogar de vida” en el cantón Pujilí - Cotopaxi - Caicedo Romero, Hugo Marcelo (2022)
The objective of this work is to improve the quality of life of the elderly and residents of the "Hogar de Vida" Nursing Home, through the implementation of a home automation system, which is focused on the comfort and well-being of this geriatric group. The implementation of this system refers to home automation circuits connected through a wireless network and smart devices that allowed improving the quality of life of this vulnerable group of society. By installing smart electronic devices, it is possible to improve energy management focused on reducing electricity consumption. Exterior security, as well as communication, is now improved with the installation of a video intercom which covers a distance of 15 meters from the main door to the garage. The comfort of the elderly is specifically addressed to the lighting system and cold temperatures in the rehabilitation area, which by providing a heater now maintains an optimal temperature for the activities carried out in this area. In addition, the economic-financial analysis was prepared that allows us to demonstrate the total amount of investment and the recovery time of the same.